👤

Descompune in factori : 
a.) x²+6×+9
b.) 4b²+9a²-12ab
c.) 5-2√5×+x²



Răspuns :

Este formula:
[tex] a^{2} +2*a*b+ b^{2} = (a+b)^{2} [/tex]
respectiv:
[tex] a^{2} -2*a*b+ b^{2} = (a-b)^{2} [/tex]

a) [tex] x^{2} +6*x+9[/tex]=
=[tex] x^{2} +2*3*x+ 3^{2} =[/tex]
=[tex] (x+3)^{2} [/tex]

b) [tex]4* b^{2} + 9* a^{2} -12*a*b=[/tex]
=[tex](2* b)^{2} + (3* a)^{2} -2*(3*a)*(2*b)=[/tex]
=[tex] (2*b-3*a)^{2} [/tex]

c) [tex]5-2* \sqrt{5} *x+ x^{2} =[/tex]
= [tex]( \sqrt{5} )^{2} -2* \sqrt{5} *x+ x^{2} =[/tex]
=[tex] (\sqrt{5}-x)^{2} [/tex]